2008
DOI: 10.1007/s10826-008-9212-3
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Aggression: The Relationship Between Gender and Abuse Experience in Youngsters Referred to Residential Treatment

Abstract: We examined the relationship of gender and different forms of abuse experience on internalizing symptoms, externalizing symptoms, and IQ in a sample of 397 youngsters who were admitted to a residential treatment program. Three types of abuse experience were examined in this study: sexual abuse only, physical abuse only, and both sexual and physical abuse. Results indicate that girls exhibited higher levels of internalizing and externalizing symptoms even though abuse experience was accounted for in the analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
3
10
0
Order By: Relevance
“…Unfortunately, underreporting likely dampened the abuse effects reported in this study, so results demonstrating significant abuse effects are particularly noteworthy. We used widely accepted and well‐validated outcome measures, including the DISC and the CBCL, which improve upon measures used in similar studies (e.g., Connor et al., 2004; Doerfler et al., 2009). Additionally, our sample size utilizes a large total N and boasts strong sample sizes for all areas except for boys with sexual abuse histories, where our power is more limited.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, underreporting likely dampened the abuse effects reported in this study, so results demonstrating significant abuse effects are particularly noteworthy. We used widely accepted and well‐validated outcome measures, including the DISC and the CBCL, which improve upon measures used in similar studies (e.g., Connor et al., 2004; Doerfler et al., 2009). Additionally, our sample size utilizes a large total N and boasts strong sample sizes for all areas except for boys with sexual abuse histories, where our power is more limited.…”
Section: Discussionmentioning
confidence: 99%
“…US researchers have recently commented on the ongoing lack of attention in the research literature to gender differences in residential care, despite the fact that treatment programme outcomes show that girls have more severe dysfunctions than boys after completing such programmes (Doerfler et al 2009;Connor et al 2004). Both the first systematic study of the relationship between gender and the abuse of young people placed in residential care in the US (Doerfler et al 2009) and a study of 397 new placements in a Massachusetts residential institution (Connor et al 2004) show that girls entering residential care have more psychological disorders than boys and display both greater internalizing and externalizing behaviour.…”
Section: Gendermentioning
confidence: 99%
“…In addition, girls seem to profit less from residential treatment compared to boys (Frensch and Cameron 2002). These findings suggest that boys and girls admitted to residential treatment might need a different approach (Connor et al 2004; Doerfler et al 2009). Surprisingly, as far as we know, previous studies have not included group composition in terms of sex as a predictor of outcome success of residential treatment for adolescents with severe behavioral problems.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies showed that girls entered residential institutions with more severe problem behavior. Specifically, girls demonstrate higher rates of individual problem behaviors and come from more dysfunctional families (e.g., Connor et al 2004 ; Doerfler et al 2009 ; Handwerk et al 2006 ; Nijhof 2011 ). Girls are also more likely to have sexually traumatic experiences, such as sexual abuse (e.g., Doerfler et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation